Inside the black box: How business model innovation contributes to digital start-up performance - Hai Guo; Anqi Guo; Hongjia Ma (Journal of Innovation & Knowledge (JIK), 2022)
Business model innovation is critical to firm survival and success. Digital revolution has reshaped value-creation methods in recent years, spawning various novel business models. However, we still have limited understanding of how a start-up's business model innovation efforts translate into superior performance in the digital economy. Drawing on insights from the demand-side perspective, this study disassembles the business model innovation architecture into three elements—value proposition, value creation, and value capture innovation—and investigates how business model innovation contributes to digital start-up performance. Based on a survey of Chinese digital start-ups, we find that value proposition innovation is positively related to digital start-up performance. Moreover, this relationship is mediated by value creation and value capture innovation. This study contributes to business model research by examining the impact mechanism of business model innovation on firm performance and providing new insights into the demand-side perspective of business model innovation.
Keywords: L10; M10; M13; O30; O32; 650; Business model innovation; Demand-side perspective; Digital start-up; Value capture; Value creation; Value proposition